Plantar fasciitis injury status influences foot mechanics during running. (July 2022) - Wiegand, Kristyne; Tandy, Richard; Freedman Silvernail, Julia
Abstract: Background: The biomechanical factors related to plantar fasciitis are not well understood. A history of injury is considered a risk factor for subsequent injury, but it is unknown if differences in mechanics exist before, during, and after injury. This study compared gait mechanics among individuals with plantar fasciitis, resolved plantar fasciitis, and uninjured controls. Methods: Thirty male and female runners were divided into three groups: 1) plantar fasciitis ( n = 10, age 43 ± 11 years); 2) resolved plantar fasciitis ( n = 10, age 43 ± 13 years); and 3) control ( n = 10, age 38 ± 11 years). Participants ran at preferred velocity and 3.3 m/s while kinematics and kinetics were collected. Variables of interest include vertical loading rate, foot, ankle, knee, and hip kinematics, arch height index, arch rigidity index, and arch drop. Group differences were analyzed at each velocity using one-way analysis of variance. Findings: The plantar fasciitis group exhibited less forefoot extension ( P = 0.02), more midfoot inversion ( P < 0.01), and more midfoot extension ( P < 0.01) than the resolved plantar fasciitis group. Foot mechanics in controls did not differ. Sagittal knee range of motion was greater in the plantar fasciitis group than resolved or control ( P = 0.01). No other variables were significantly different among groups. Interpretation: The plantar fasciitis group exhibited dynamic foot mechanics which suggest a lower, more flexible arch compared to the resolved group, although static measures of foot structure and ankle motion did not differ. The differences between these groups indicate that the motion of the forefoot and midfoot during gait are important to consider for plantar fasciitis. Highlights: Altered foot mechanics exist in runners with plantar fasciitis. Differences in mechanics were noted between current and resolved plantar fasciitis. A lowered arch during running may cause or prolong plantar fasciitis symptoms.